Ultra-structural analysis of the brain in a Drosophila model of Alzheimer's disease using FIB/SEM microscopy. (18th September 2013) - Park, Se Jin; Schertel, Andreas; Lee, Kyung Eun; Han, Sung Sik
Abstract: Alzheimer's disease (AD), one of the most prevalent neurodegenerative brain diseases, has been extensively researched for years. However, its synaptic structure, which is a basis for understanding neurodegenerative disorders, has not yet been understood clearly. Defining the structures of neurons and their synaptic connections is the significant goal of brain research. To study synaptic connectivity, three-dimensional (3D) reconstructions of the nervous system are very helpful. In this study, the 3D structure of brain synapses in the Drosophila melanogaster Swedish amyloid precursor protein (APP) mutant, which is characterized by early onset AD, was analyzed using focused ion beam/scanning electron microscopy (FIB/SEM). This technique is one of the most useful for 3D reconstruction, as the process of obtaining serial images is fully automated and thus avoids the problems inherent in hand-operated ultrathin serial sectioning. The 3D images of normal and AD brains reported in this study reveal characteristic features of AD such as appearance of autophagy, abnormal axon formation and increased mitochondrial size. This 3D analysis reveals structural change as a basis for understanding neurodegenerative disorder.